Electrical activity in white adipose tissue of rat (Revista Española de Fisiología, 1990)
Intracellular recording of white adipocytes was performed in an in vitro preparation. Resting potential, input resistance and membrane time constant averaged: -34 +/- 9 mV, 295 +/- 161 M omega, and 58 +/- 19 ms respectively (mean +/- SD, n = 32). Intracellular injection of positive and negative square current pulses elicited membrane voltage responses, characterized by a rectification of the voltage change evoked by positive pulses, and a slow return to baseline at the offset of hyperpolarizing pulses. The amplitude and duration of the slow return to resting potential was dependent on membrane potential, pulse duration, and extracellular K+ concentration. This response was depressed when external Ca2+ was replaced by Co2+, and by external application of 4-aminopyridine. These results indicate that white adipocytes can generate membrane voltage responses which may mostly be a consequence of the activity of ionic channels. The properties of the slow return to baseline suggest that it may be due to a transient K+ current.